The winning link a proven process to define, align, and execute strategy at every level - Taylor, Billy (McGraw Hill Education, 2022)
"Give ownership of business strategy to every employee at every level of your organization"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Strategic planning -- Employee participation; Employee empowerment; Planification stratégique; Participation du personnel; Personnel; Habilitation; Strategic planning; Employee participation